Soil CO2 emission and carbon budget of a wheat/maize annual double-cropped system in response to tillage and residue management in the North China Plain. Issue 3 (4th May 2017) - Wu, Lan-Fang; Li, Bin-bin; Qin, Yue; Gregorich, Ed
ABSTRACT: To investigate the impacts of tillage and crop residue managements on soil CO2 emission and C budget in a wheat ( Triticum aestivum L.)/maize ( Zea mays L.) double-cropped system in the North China Plain (NCP), a field experiment was conducted consisting of four treatments: tillage with crop residues retention (CT+), tillage with crop residues removal (CT−), no-till with crop residues retention (NT+), and no-till with crop residues removal (NT−). Daily soil CO2 fluxes changed with crop growing stage and peaked during the most vigorous growth of period, fluxes in maize season were higher than those in wheat season. Compared to the tilled soils, cumulative CO2 emissions were significantly lower under no-till treatments. The largest cumulative CO2 emission occurred under CT+ (65 g CO2 -C m −2 y −1 ) and the smallest was under NT+ (39 g CO2 -C m −2 y −1 ). After 5 years of the experiment, soil organic carbon (SOC) sequestration were greater with crop residues retention (CT+ and NT+) than with crop residues removal (CT− and NT−), the maximum SOC stock was in NT+ (5940 g C m −2 ) while the minimum was in CT− (3635 g C m −2 ). NT+ could help to mitigate CO2 emission in the annual wheat/maize double-cropping system of the area.